Archaeological Investigations of the State Hermitage Museum at the Site of Nymphaion in 2019 and 2021 - Novoselova, Nadezhda; Sokolova, Olga (Hyperboreus, 2024)
The review focuses on archaeological research of the State Hermitage Expedition on the site of Nymphaion in 2019 and 2021. The site is located on Kamysh-Burun Cape, 17 km southwest of Kerch center (Russian Federation, Republic of Crimea, Eltigen District). The works were concentrated in two locations of the site, Sector M and Sector O. In Sector M, an ancient theater constructed in the first half of the 4th century BC was studied. In Sector O, a main city street and gate towers became the subjects of research.